2021
DOI: 10.1007/s10741-021-10117-6
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial assist device for heart failure with preserved ejection fraction: initial results with torque control mode in diastolic heart failure model

Abstract: A novel pump, the left atrial assist device (LAAD), is a device specifically for the treatment of heart failure with preserved ejection fraction (HFpEF). The LAAD is a mixed-flow pump that is implanted in the mitral position and delivers blood from the left atrium to the left ventricle. During the development process, we aimed to explore whether device activation in torque control (TC) mode would improve the function of the LAAD. The TC mode causes adjustment of the pump speed automatically during each cardiac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Miyagi et al developed a similar MCL to that presented in this work for testing of the Left Atrial Assist Device (LAAD) for the treatment of HFpEF (9). In this study, Miyagi et al used a mock ventricle (AB5000, ABIOMED Inc., Danvers, MA) in conjunction with a static blood reservoir representing the left atrium, and adjustable afterload and compliance simulators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Miyagi et al developed a similar MCL to that presented in this work for testing of the Left Atrial Assist Device (LAAD) for the treatment of HFpEF (9). In this study, Miyagi et al used a mock ventricle (AB5000, ABIOMED Inc., Danvers, MA) in conjunction with a static blood reservoir representing the left atrium, and adjustable afterload and compliance simulators.…”
Section: Discussionmentioning
confidence: 99%
“…This is challenging as HFpEF is a multifactorial disease, typified by four phenotypes (8) which makes the simulation of the condition challenging. Previous attempts at developing a mock circulatory loop (MCL) have utilized single pneumatic chambers (9,10), piston actuated ex-vivo hearts (11, 12), and external drive motors (13). The problems with ex-vivo heart models have been well documented; namely the rapid deterioration of electrophysiological and hemodynamic functions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, atrial suction and other adverse events were rare and likely due to the relatively small size of the calf’s left atrium, whereas no evidence of LV outflow obstruction was reported. Miyagi et al ( 181 ) also explored the effect of alternative pump control options. Torque control of the LAAD was maintained in a mock circulatory loop, and the pump speed of the device was adjusted by using active torque control.…”
Section: Device-based Solutions For Hfpefmentioning
confidence: 99%
“…Although the LAAD has been shown to ameliorate the hemodynamics of HFpEF in a variety of studies ( 177 , 178 , 179 , 180 , 181 ), questions remain regarding the site of implantation of the device, as the implications associated with the removal of the mitral valve have yet to be assessed ( 182 ). In addition, although implantation at the supra-valvular level has been suggested to preserve the mitral valve, this configuration has not been studied thoroughly ( 181 ). Finally, the effects of this device on LV diastolic function should be investigated further in in vivo studies to more comprehensively evaluate the feasibility of the LAAD for the treatment of HFpEF.…”
Section: Device-based Solutions For Hfpefmentioning
confidence: 99%
“…Finally, the LAAD is a continuous pump for implantation at the mitral valve designed to decompress the LA and is the only one of these devices undergoing animal investigation. In these studies, the LAAD was shown to effectively increase CO and mean aortic pressure (MAP) and decrease LAP ( Fukamachi et al, 2020 ; Kado et al, 2020a , b ; Miyagi et al, 2021a , b ).…”
Section: Introductionmentioning
confidence: 99%